Desafios na leitura de textos de especialidade em língua estrangeira : perceções de professores-estudantes em formação inicial - Tomé, Simone Auf der Maur (Linguarum Arena, 2017)
This article aims to shed light on the diffi culties encountered by students as readers of scientifi c texts in a foreign language, in this case in German. The focus of study lies on the perspectives of three Portuguese students-teachers in initial training who participated in activities for the development of their receptive textual competence in the context of the German didactic seminars held over two semesters at the Faculty of Letters of the University of Porto (FLUP). The work was conceived as a qualitative study to collect what the study participants thought and felt about their readings of scientifi c texts written in German. Data were obtained from a questionnaire, protocols of retrospection, verbal protocols and a semi-structured interview at the end. The results obtained by comparing the three cases, revealed that students found signifi cant diffi culties, not only in relation to the texts as specific academic documents, but also for themselves as readers, identifying knowledge gaps and a lack of habit in the processing of these types of texts. Based on these results, the aim is, ultimately, to equate the most appropriate teaching performance to the characteristics of these students and the texts to be read.